Sociodemographic and Clinicopathological Features of Lymphoma Patients in Indonesia: A report from Special Region of Yogyakarta Province - Anggorowati, Nungki, Indrawati; Dhyanti, Amira L; Arkananda, Hafidh; Rizki, Salsabilla Hasna; Setiawan, Syahru Agung; Bagaskoro, Miraz Radhea; Hardianti, Mardiah Suci (Asian Pacific Journal of Environment and Cancer, 2022)
Introduction: Lymphoma as a heterogeneous disease has various characteristics not only in the clinical manifestation but also in sociodemographic aspect. Epidemiological data with sociodemographic description in lymphoma is still unexplored. Objective: This study aimed to provide updated and detailed description of lymphoma with emphasis on patient characteristics, sociodemographic data and hematologic findings. Materials and Methods: This was an observational descriptive study with a cross-sectional design. The data were from the medical records in Dr. Sardjito Hospital, a national referral hospital in the Special Region of Yogyakarta Province Indonesia from 2012 to 2018. All lymphoma patients > 18 years were included. Patients’ characteristics, socio-demographic indicators, tumor characteristic and hematological finding were recorded. The difference of socio-demographic, clinical and laboratory characteristics between Non Hodgkin Lymphoma (NHL) and Hodgkin Lymphoma (HL) was analyzed with Chi-Square, Fisher-Exact, and Mann-Whitney test (P <0.05 was statistically significant). Results: There were 675 cases. Male predominated, mean age at diagnosis was 54.1 for NHL and 42.3 for HL. There was significant difference in the mean of age (p=0.000), occupation (P=0.035) and educational level (P=0.020) between NHL and HL patients. B cell NHL was found to be the most common type of lymphoma, with DLBCL being the most common histopathological type. Hematological findings were found to be within the normal range. Conclusion: There are significant difference in the mean of age, occupation and education level between NHL and HL patients. Further study to explain the scientific reasons of the difference are required.